Exploring FeMnVAl Heusler Alloy: Physical, Mechanical, and Magnetic Properties - Ray, R. B.; Rai, R. K.; Yadav, D. K.; Kaphle, G. C. (Journal of Lumbini Engineering College, 2024)
The structural, mechanical, electronic, and magnetic properties of equiatomic quaternary Heusler alloy FeMnVAl have been investigated using first-principles approach. This alloy shows ferromagnetic ground state structure with chemical stability indicating compound fulfills the criteria for synthesizing experimentally. The calculated values of Pugh’s index and Poisson’s ratio confirmed ductile nature of FeMnVAl. The investigation of band structure and density of states validates the behaviour of half[1]metallic ferromagnetism (HMFs), which follow the Slater-Pauling rule Mt = Zt - 24 and have a magnetic moment value of around 1 μB/f.u. Its features also allow for potential applications in the realm of spintronics devices and optoelectronics.